(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Cellulitis and Psoriasis are common bacterial skin infections. Psoriasis affects 1-3 percent of the world’s population. According to Ayurveda, it is a curable disease, and leech therapy, a bloodletting method is considered the effective method in the treatment of psoriasis and cellulitis with no side effects. To evaluate the efficacy of leech therapy, Ayurvedic medicine, and lifestyle modification in the management of psoriasis complicated by recurrent cellulitis and other co-morbidities. This is a case report of a known diabetic and obese 39-year-old female patient. An Ayurvedic management plan and dietary modifications with leech application were administered to the patient. Leech application was done in five sessions with regular follow-ups. Leech therapy showed outstanding results in producing symptomatic relief for patients. It has helped the patient in reducing the condition of Psoriasis and Cellulitis with no common steroid therapy complications like weight gain and hyperglycemia. In this study, leech therapy showed excellent results in producing symptomatic relief for the patient. Leech therapy has a considerable anti-psoriatic and anticellulite impact without causing any toxicity or side effects.